A two-year review of suicide ideation assessments among medical, nursing, and pharmacy students. Issue 4 (4th July 2017) - Mospan, Cortney M.; Hess, Rick; Blackwelder, Reid; Grover, Susan; Dula, Chris
ABSTRACT: Suicide is the 10th leading cause of death in the U.S. and has increased in prevalence during the past 15 years. Patients who attempt suicide are more likely to have contact with their primary care provider than a mental health provider in the month before attempting suicide, highlighting the need for competency in suicide ideation (SI) assessment. The Communications Skills for Health Professionals is an interprofessional course involving first-year medical, nursing, and pharmacy students. Specific instruction regarding assessment of SI was delivered through an online module and later practiced by students with standardized patients (SP). A final Objective Structured Clinical Examination featured an SP with depression, but without SI, though an assessment of SI was indicated. Three hundred fifty six interviews were reviewed and 55.1% (196/356) of students assessed for SI. Across professions, 65.5% (93/142) of medical students, 52.5% (32/61) of nursing students, and 46.4% (71/153) of pharmacy students performed an assessment. Medical students' SI assessment was highest across the groups ( p = 0.001), while pharmacy students' SI assessment was lowest ( p = 0.004). Results suggest that additional educational strategies should be developed and implemented to increase SI assessment performance in all professions, but especially in pharmacy students.